Um olhar de colonial sobre a imprensa brasileira: dos embates políticos no século XIX às novas possibilidades de expressão no digital - Bruno, Ligia Vieira (2024)
This dissertation aims to study the role of the press in Brazil through the lens of the decolonial thinking, seeking to understand how the decolonial epistemology can encourage the search for new sources for the media that circulates in digital journalism, as well as whether it is capable of generating a reflection on the format of communication in Brazil, consolidated by eurocentric & positivist guidelines. This research traces a historiographic line from the invention of the printing press in Europe in the 15th century, which precedes the advent of mercantile capitalism and the beginning of colonization processes in Brazil, going through the consolidation of the brazilian press in the 19th century, on the way to the Republic, and in constant dialogue with the positivist ideas of the Modernity that was solidifying in Europe, and getting to the press in the digital world of the 21st century, and the possibilities that arise with the greater democratization of knowledge in the digital environment- and to the possibility of the Decolonial thinking, which seeks to reverse cultural guidelines established in the media since our recent colonial past